Asymmetrical neural adaptation in lower leg muscles as a consequence of stereotypical motor training - Ogawa, T.; Kawashima, N.; Suzuki, S.; Nakazawa, K. (Journal of Motor Behavior, 2012)
Despite well-authorized facts regarding asymmetrical architectural changes between different limbs after persistent participation in particular motor training, no studies have addressed the neural aspects to the present. The authors undertook the study to elucidate the possibility of neural adaptation on a limb-by-limb basis after repetitive engagement in a particular motor training routine. We investigated lower leg muscles in endurance-trained track runners who have been trained by routinely running on a trackin counterclockwise direction on curved paths. Stretch reflex responses in the plantarflexor muscles (soleus [SOL], medial [MG], and lateral head of the gastrocnemius muscle) were evaluated bilaterally with participants sitting at rest. Comparisons were made between homonymous muscles of the right (corresponding to outside leg for track running) and left leg (inside leg, likewise) and with a group of nontrained controls. The result clearly demonstrated that the responses were prominently different between the legs (thus,asymmetrical) in the MG muscles and partially in the SOL muscles in the trained group. In contrast, no such differences were obtained in the nontrained control group. The result demonstrated that neural adaptation took place asymmetrically and that could be attributable to their repetitive engagement in the stereotypical motor task.